When men migrate for marriage: negotiating partnerships and gender roles in cross-border marriages between rural Kosovo and the EU. Issue 2 (25th January 2021) - Leutloff-Grandits, Carolin
ABSTRACT: In Western hegemonic discourses, cross-border marriages in which ethnic minority members, especially Muslims, take a partner from a 'country of origin' are framed as patriarchal and backward and women are portrayed as victims within such marriages. Based on long-term ethnographic fieldwork, the article focuses on the marriages of men from rural Kosovo, who have moved to Austria or Germany because they married a woman from a 'Kosovan' background, and on the gender roles that are negotiated here. The men in these cross-border marriages do not fit into the dominant Western image of 'patriarchal' ethnic-minority men. After migration, married male migrants find themselves in multiple dependencies and take up diverse roles that are framed by their educational profiles and economic performance, by the support they receive from their wives, as well as the diverse and partly translocal social fields they relate to. Depending on their social position, male marriage migrants may be doubly marginalised, by the majority society as well as within their ethnic communities. But men with higher education who successfully integrated into the labour market may also set up intra-ethnic boundaries, be it to members of their rural community in Kosovo or within ethnic-minority communities in Austria or Germany.